Fédéralisme déguisé ou ajustement marginal ? L’impact de la dévolution sur le système politique britannique - Michael Tatham (Revue Française de Civilisation Britannique)
Many academic and political observers find parallels between devolution and federalism unconvincing. The United Kingdom would thus remain a unitary state which would only have allowed some marginal adjustments at its periphery. However, using a seven-point definition of federalism, we draw different conclusions. We argue that devolution has deeply federalised the United Kingdom’s governmental structures and practices. Though it does not strictly adhere to it, the British political system is now closer to a federal model of government.